(untitled) (Journal of Engineering, 2010)
Casting defects are ones of the important problems occurring in the casting process .The large number of the defects make the diagnosis of them difficult and depend on the inspector experience and his information of the defects property. This diagnostic perhaps being wrong and not accurate. Therefore in this research an inclusive program through information system was designed to diagnose the defects and its causes then put the suggested remedy, this program contains four methods to recognize the defects in castings .The methods are 1.Use selection of the listed property of the defects 2.Benefit from the pictures of defects to diagnose the defect. 3. The questions and answers method .4.Combo box that contains all the defects name .The last method was designed only for the workers having a great experience in this field. It is found after verification that the method of picture is the simplest and rapidly one because the user needs to see the picture that is given to him and compare them with the castings defect. The program was designed by the use of Visual Basic language, which allows making dealing with the methods easy. The arrangement of this number of defects was done by use general classification that classify them to seven groups and these were divided to subdivision groups .The verification was done to check the effectiveness of the program and it gave good results .